PENGARUH KOMBINASI ACTIVE LOWER RANGE OF MOTION DAN HEEL RAISE EXERCISE TERHADAP RISIKO ULKUS KAKI - Riska Apriani; Khoirul Latifin; Dhona Andhini (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Non-communicable diseases (PTM) were currently a public health problem, one of them was Diabetes Mellitus (DM). DM type 2 one of the common, which is more than 90-95% and the fourth most prevalent PTM in South Sumatera with 4.386 cases. The problem that was often experienced by DM patient was the continued effect of hyperglycemia that caused peripheral neuropathy and could caused foot ulcers to have amputations. The longer a person was DM, more to had complications. The combination of active lower range of motion and heel raise exercise was one of physical exercise carried out by moving the lower extremities so that blood flow could smooth and transported nutrients to the peripheral. This study aimed to find out the effect of combination active lower range of motion and heel raise exercise on the risk of foot ulcer on typed 2 DM patient. This was a pre-experimental design with a one-group pretest-posttest. Intervention carried out for 6 days with a practice in the morning and evening. The samples through purposive sampling method were 16 people. The results before the intervention 43,8%n of respondents moderate risk and after intervention became low risk (75%). Analysis of marginal homogeneity statistical test showed that there was a significant influence on the risk of foot ulcer before and after intervention of combination active lower range of motion and heel raise exercise (p value 0,001), and there was a relation between compliance medication (p= 0,01), smoking status (p= 0,005) on the risk of foot ulcers. To reduce the risk of complications on DM patient, combination active lower range of motion and heel raise exercises could be applied independently to reduce the risk of diabetic foot ulcers.